Unveiling the Hidden Connection: Investigating the Relationship between Drug Craving, Emotional Manipulation, and Interoceptive Awareness for Social Acceptance among Substance Use Disorder At KSA - Fahad Ali AL otaiby; Fahad Awadh Alghdhbani; Naif Falah Alboqami; Najeah Mashai M Alanazi; Adel Ali Hussain AL Hussain; Ayedh Bliheen Alkhtani; Thuwaini Hameed Alrashidi; Khaled Hamad J Almohammad; Saeed Shaie Alqahtani; Muteb Muways Almutairi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Drug addiction is a chronic condition that causes relapses of intoxication, bingeing, withdrawal, and cravings. substance addiction is characterized by a continuous cycle of seeking and consuming the substance, Aim of the study :This study aim to assess the level of drug craving , emotional manipulation and the relationship interoceptive awareness for social acceptance among substance use disorder. Methods: Design:Descriptive, cross sectional, correlational, quantitative. Research design was utilized to conduct this research Setting :This study was conducting at 5 Saudi addictive therapeutic communities settings, at Riyadh, Dammam ParticipantsA convenience sample of 200 individuals with drug use disorder was drawn from a larger sample of 400 registered patients who visited the clinic. Instrument: Three tools were utilized ; The Penn Alcohol Craving Scale (PACS) ,The Emotional Manipulation Ability Scale , The Perceived Acceptance Scale Results:A significant majority of respondents report high levels of craving(76%) for substancesMost respondents exhibit a strong ability to manipulate emotions(65%), either their own or others’A very small percentage of respondents(10%) feel accepted or perceive social support from their environment. The majority of individuals reported significant levels of emotional manipulaion and low social acceptance from their parents, families, and friends, which supports previous findings. Conclusion:Based on the results of the Penn Alcohol Craving Scale (PACS), there is a significant relationship between emotional manipulation ability and alcohol craving, with a moderate positive correlation (rs = 0.574, p < 0.011). This suggests that individuals with higher emotional manipulation abilities may experience stronger cravings for alcohol. On the other hand, the perceived acceptance scale shows a negative correlation with alcohol craving (rs = -0.434, p = 0.024), indicating that individuals who perceive higher levels of acceptance may experience lower cravings for alcohol.